Prevalencia de la dirofilaria immitis en perros de la parroquia Quiroga del cantón Bolívar, 2021 - Vera Bravo, Bertha Irene (2022)
The present research work was carried out in Quiroga parish, Bolívar canton in Manabí province, with the objective of evaluating the prevalence of the heartworm (Dirofilaria immitis) diagnosed by the thick smear method. The study was descriptive, not experimental, the finite population formula was used with 90% confidence and 10% error to obtain the size of the sample to be collected, where the population size was taken according to the last rabies vaccination census in Quiroga parish, then the percentage method was used to determine the percentage of positive animals and the χ2 test (Chi-square) of independence at 5% significance to identify the relationship between the variables (age, sex and genetic group). 64 dogs were used as study units, with apparent normal physiological status between the months of May and June 2021. Among the results, 11 positive cases were found, which represented a prevalence of 17.19% of Dirofilaria immitis and the raised hypothesis. The presence of Dirofilaria immitis does not have any type of relationship with the study variables, it acts independently, the vectors are capable of transmitting the disease to dogs without distinction of sex, age or genetic group.